USING PEDOTRANSFER FUNCTIONS TO PREDICT SATURATED HYDRAULIC CONDUCTIVITY FOR LAYERED SOIL PROFILES A CASE STUDY AT THE SOKOINE UNIVERSITY OF AGRICULTURE FARM, TANZANIA - Mulengera, M. K.; Mdemu, M. V.; Mtakwa, W. P. (Tanzania Journal of Engineering and Technology, 2018)
Abstract